Analisis Sosiologi Hukum Islam pada Warung Kopi Lesehan yang Mempekerjakan Perempuan demi Meraup Cuan Maksimal di Jalan Suromenggolo Ponorogo - Umaya, Roin; Nafi’ah, Nafi’ah (Fakultas Syariah INSURI Ponorogo, 2020)
Maximizing “cuan or profit” in a business is a necessity. Traders often memorize all means in marketing their merchandise. Likewise, coffee sellers on Suromenggolo street or new road in Ponorogo Regency. In attracting customers they deliberately involve